USER BEHAVIOR IN THE HAJI PINTAR APPLICATION USING THE TECHNOLOGY ACCEPTANCE MODEL APPROACH - Hadi, Miftahul; Aprilia, Rachma; Arianty, Erny; Darmawan, Muhamad Harestya (Institut Agama Islam Negeri Metro, 2025)
This study aims to analyze the factors influencing the acceptance of the Haji Pintar application by users or prospective pilgrims using the technology acceptance model, which consists of three variables, namely intention to use, perceived usefulness, and perceived ease of use. This study adopts a quantitative approach. The target population comprises users of the Haji Pintar application, with sample data collected via online questionnaires distributed using an accidental sampling method, a type of non-probability sampling. The collected data will be processed through using the SmartPLS software. The results show that two of the three proposed hypotheses received support at a significance level 0.05. Specifically, it was determined that perceived ease of use positively and significantly influences perceived usefulness and the intention to use. At the same time, one hypothesis was rejected, indicating that perceived usefulness does not significantly affect the intention to use. Overall, Haji Pintar app users consider the application easy to use, which may increase their desire to use it again. However, the application has not yet provided significant usefulness, which may be a consideration for further development and improvement of the Haji Pintar application.